Measures Adopted by Romania Against the Negative Effects of Fiscal Competition and Trends of Fiscal Harmonization in the European Union - Camelia Madalina BELDIMAN (Communications of International Proceedings, 2023)
This paper aims to analyze the concept of tax competition, as well as the challenges currently facing Romania compared to the economy of the Member States to find the best solution to ensure a fair tax system for all EU citizens and for all businesses. I will emphasize EU efforts to address tax competition issues by implementing policies in each Member State to prevent tax fraud and evasion, thus encouraging the free movement of people and capital, increasing the number of secure cross-border transactions, thus ensuring effective coordination of the functioning of the single market. I will provide some arguments for and against tax competition where the main causes of tax competition are identified, the analysis focusing mainly on the impact of globalization, and finally the effects of competition on economic factors, but also those of a political nature are analyzed. The tax race might be seen as an approach to gain largescale competitiveness. As there is pressure to reduce tax rates and budget spending, tax battle might be judged as a significant element in sustaining the development of the global economy. With the economic downturn, fiscal policy has been assessed with more interest, as it was expected to be effective in the economic recovery. High-level economic augmentation has narrowed Romania's improvement hiatuses compared to other EU countries.
Keywords: Fiscal Policy; Fiscal Competitiveness; Fiscal Taxes and Duties; World Economy; Fiscal Monopoly